Quantification of ongoing APOBEC3A activity in tumor cells by monitoring RNA editing at hotspots - Pégah Jalili (Nature Portfolio, 2020)
The DNA cytosine deaminases APOBEC3A and APOBEC3B have emerged from cancer genomics studies as drivers of mutation in cancers and tumor heterogeneity. Here the authors present a computational approach to identify the RNA mutations specifically driven by APOBEC3A, and developed an RNA mutation-based assay to quantify ongoing APOBEC3A activity in tumor cells.